PENDIDIKAN, GLOBALISASI, DAN AKHLAK - Miftahuddin Miftahuddin (LPMPP Universitas Negeri Yogyakarta, 2008)
Globali ation has started. People all over the worlddepend on each other in allaspects, such as cultural, economic,and political aspects. In the cultural aspect, inparticular, the cultural boundaries have blurred. This era is a challenge for the fieldof education. For that reason, this article tries to emphasi e the importance of moralvalues as the main concern in the educational process. To preparehuman beingswho possess moral values in the globali ation era, educational institutions still playimportant roles although they are not the ones. All segments in society, mainlyfamilies,must prepare human sources with moral integrity. In reality, educationalinstitutions have double roles; on the one hand, theymust prepare learners withgood personality, and on the other, they must prepare learners to be competitive inthe dynamics ofthe global world s challenge